(untitled) (Proceedings of the International Conference on Education, 2021)
Monarch Route was a university award-winning project, having won the Premios Latinoamerica Verde in 2018. The project followed a research-based methodology and implemented a vertically integrated collaboration which included 181 undergraduate students; the entire student body enrolled in the Sustainable Development Engineering course of the Tec de Monterrey, Campus Santa Fe, in 2017. It was conducted in conjunction with the Fundación Nacional para la Conservación del Hábitat Boscoso de la Mariposa Monarca A.C. (FUNACOMM) so as to stop and revert the extinction of the monarch butterfly and at the same time promote benefits for the rural communities found throughout the migratory route of this species. The purpose of this work is to inspire the academic community to design successful projects which develop transverse and disciplinary competences. The project answered the following research question: What are the learning outcomes from participating in a project with real life impacts, working in a vertical and horizontal collaboration system? Using a mixed methodology, we describe the details of the implementation and learning outcomes. The Monarch Route project intrinsically motivated the students since it allowed them to collaborate, vertically and horizontally, in a socially relevant project, as well as having the choice and control over their education. By means of a text analysis of 22 final remarks of participating students, it was evident that they were able to recognize environmental, conservation and sustainable development problems and analyze their impact, in addition to being aware of the social aspects associated to them, and above all, recognize the link of these type of projects with their professional life and their social commitment to Mexico.